2015
DOI: 10.3389/fgene.2015.00145
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNAs: a potential novel class of cancer biomarkers

Abstract: Long noncoding RNAs (lncRNAs) are a novel class of RNA molecules defined as transcripts longer than 200 nucleotides that lack protein coding potential. They constitute a major, but still poorly characterized part of human transcriptome, however, evidence is growing that they are important regulatory molecules involved in various cellular processes. It is becoming increasingly clear that many lncRNAs are deregulated in cancer and some of them can be important drivers of malignant transformation. On the one hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
181
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(183 citation statements)
references
References 115 publications
1
181
0
1
Order By: Relevance
“…Accumulating evidence revealed disruptive expression of lncRNAs in various types of human cancers, and these lncRNAs are capable of regulating diverse cellular processes such as tumor cell growth, cell apoptosis, cell invasion and metastasis, and tumor cells sensitivity to chemotherapy drugs 24, 25. Moreover, a growing number of studies have demonstrated that dysregulated lncRNAs have been identified as critical regulators during the tumorigenesis and cancer progression, and some of these lncRNAs are determined as significant factors for clinical implication.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence revealed disruptive expression of lncRNAs in various types of human cancers, and these lncRNAs are capable of regulating diverse cellular processes such as tumor cell growth, cell apoptosis, cell invasion and metastasis, and tumor cells sensitivity to chemotherapy drugs 24, 25. Moreover, a growing number of studies have demonstrated that dysregulated lncRNAs have been identified as critical regulators during the tumorigenesis and cancer progression, and some of these lncRNAs are determined as significant factors for clinical implication.…”
Section: Discussionmentioning
confidence: 99%
“…18 Their expression profiling in various cancer types have been widely examined, and many of these lncRNAs were correlated with cancer diagnosis and prognosis. 19 A study was performed with a total of 1240 patients from 15 articles that were included, and the results indicated that a significantly shorter over survival time was observed in patients with high expression level of UCA1 in various cancers. 20 Overexpression of lncRNA UCA1 promoted osteosarcoma progression and correlates with poor prognosis.…”
mentioning
confidence: 99%
“…The expression of lncRNA C22orf32-1 was significantly upregulated in primary NPC tissues compared with the normal nasopharyngeal epithelial tissues, and therefore may act as an independent biomarker for early diagnosis and provide a novel therapeutic target for NPC (13,22,23). In the present study, the expression levels of lncRNA C22orf32-1 in 24 primary NPC tissues and 24 normal nasopharyngeal epithelial tissues were examined with one NPC and one normal nasopharyngeal epithelial cell line.…”
Section: Introductionmentioning
confidence: 99%
“…As the non-coding RNAs do not serve as the template for protein synthesis, they are considered superfluous in transcription. Multiple previous studies have demonstrated that lncRNAs take part in the development of numerous diseases, particularly via gene silencing, cell cycle regulating, chromatin remodeling and splicing regulating (13)(14)(15). The lncRNAs are categorized into oncogenes and tumor suppressor genes according to their different functions in variety of types of malignancy (16,17).…”
Section: Introductionmentioning
confidence: 99%